Styryl Lactones from Roots and Barks Goniothalamus lanceolatus - Nurulfazlina, Edayah Rasol; Fasihuddin, Badruddin Ahmad; Mai, Chun-Wai; Nur Vicky, Bihud; Fauziah, Abdullah; Khalijah, Awang; Nor Hadiani, Ismail (SAGE Publications, 2018)
A new styryl lactone, 5R,6R-5-hydroxy-6-styryltetrahydropyrane-2-one 2 was isolated from the roots of an endemic Goniothalamus lanceolatus Miq. of Sarawak, Malaysia. Furthermore, seven previously undescribed diastereomers, 5R,6R-5-hydroxygoniothalamin 3, 5R,6R-5-acetylgoniothalamin 4, 6S,7S,8Sgoniodiol-7-monoacetate 5, 6S,7S,8S-goniodiol-8-monoacetate 6, goniofupyrone B 7, deoxygoniopypyrone B 8 and 1S,5S,7R,8S,3-endo,7-endo-(+)-8-epi-9- deoxygoniopypyrone acetate 9, along with six known styryl lactones (1, 10-15) were also isolated and characterized. 6S-goniothalamin 1 is reported for the first time from a Goniothalamus species. 1, 11 and 12 showed cytotoxic activity against human colon and lung cancer cell lines with IC50 values ranging from 2.38-7.59 µM